Home financing pricing issues in the Bay’ Bithaman Ajil (BBA) and Musharakah Mutanaqisah (MMP) - Syahwan, Syahidawati; Mohamed, Mustafa Omar; Abdul Rahman, Zaharuddin (Kolej Universiti Islam Sultan Azlan Shah, 2013)
Islamic banking in Malaysia has evolved rapidly since its first invention in 1983. Throughout 30 years of development, various products have been developed to fulfill the demands of the society both Muslim and Non-Muslim. Positive support and constructive criticisms have flourished the industry and made the product innovation to be enhanced accordingly. With regards to the products, retail financing is observed to be so dearer to the society compared to other form of financing like trade and corporate. Home financing is regarded as the most influential one since it normally affects long term commitment of the customer.Thus, this paper aims at analysing pricing issue of home financing products offered in Malaysia specifically BBA and MMP. The study uses content analysis method with intense and analytical readings of the previous texts and literatures on issues observed in the two products. The issue will then be comparatively reviewed using Maqasid-based appraisals.